2013
DOI: 10.1038/nrmicro2974
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota — masters of host development and physiology

Abstract: Establishing and maintaining beneficial interactions between the host and its associated microbiota are key requirements for host health. Although the gut microbiota has previously been studied in the context of inflammatory diseases, it has recently become clear that this microbial community has a beneficial role during normal homeostasis, modulating the host's immune system as well as influencing host development and physiology, including organ development and morphogenesis, and host metabolism. The underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
2,126
4
47

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,868 publications
(2,316 citation statements)
references
References 138 publications
31
2,126
4
47
Order By: Relevance
“…Even so, across individuals and populations, infant microbiomes generally have a higher proportion of bifidobacteria and lower species richness than adults 28 and share common functional characteristics -for example, infants typically show metagenomes enriched in genes for simple sugar breakdown and folate synthesis 4,28 . Microorganisms colonizing the gastrointestinal tract are involved in a number of vital processes 5,6,8,29 . With about 70% of the cellular component of the immune system present as gut-associated lymphoid tissue, the potential for crosstalk between microbiota and the immune system is substantial; and is likely to play a central role in enabling microbial imprinting and immune programming of the newborn microbiota 8 .…”
Section: West 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, across individuals and populations, infant microbiomes generally have a higher proportion of bifidobacteria and lower species richness than adults 28 and share common functional characteristics -for example, infants typically show metagenomes enriched in genes for simple sugar breakdown and folate synthesis 4,28 . Microorganisms colonizing the gastrointestinal tract are involved in a number of vital processes 5,6,8,29 . With about 70% of the cellular component of the immune system present as gut-associated lymphoid tissue, the potential for crosstalk between microbiota and the immune system is substantial; and is likely to play a central role in enabling microbial imprinting and immune programming of the newborn microbiota 8 .…”
Section: West 10mentioning
confidence: 99%
“…In a recent report, adults with reduced gut microbial richness had higher overall adiposity, insulin resistance, dyslipidaemia and a more pronounced inflammatory phenotype than adults with higher gut microbial richness 68 . Dysbiosis has even been associated with neurodevelopment and mental health in a series of experimental models 6 . Whether microbial West 14 variation is the cause or effect of these diseases is still the subject of conjecture, but this highlights the multisystem effects of the microbiome.…”
Section: West 13mentioning
confidence: 99%
“…The microbiota in turn affects host development, metabolism, and health (Clemente, Ursell, Parfrey, & Knight, 2012; Morgan et al., 2012; Sommer & Bäckhed, 2013; Sommer et al., 2016). Host–microbiota interactions are, thus, an important factor in vertebrate ecology and evolution (Amato, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, switching from a high‐fat/low‐fiber to a low‐fat/high‐fiber diet affects the relative abundances of several microbial taxa in humans, for example, Bacteroides and Ruminococcus , within 24 hrs (David et al., 2014; Wu et al., 2011). These diet‐related changes may increase energy extraction from food and consequently alter host metabolic pathways (Sommer & Bäckhed, 2013; Turnbaugh et al., 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Colistin supplementation is recognised for its damaging effect on E. coli strains (Lamb, 1968). The alteration of intestinal morphology due to colistin supplementation could also be associated with a deleterious effect on commensal bacteria playing a role in gut development (Sommer and Bäckhed, 2013). Yin et al (2008) reported that colistin supplementation during the 2 weeks after weaning altered the E. coli population in the jejunum and ileum, but also that of Lactobacilli colonies, which are recognised for their beneficial effect on the mucosal structure of the intestine (Mao et al, 2016).…”
mentioning
confidence: 99%